Kearifan Lokal dalam Motif Batik Kaliagung Kulon Progo: Sebuah Kajian Ekologis - Maria Vincentia Eka Mulatsih; Ridho Al Awwali Khoiromawla Judien (Corak, 2026)
The interdisciplinary study about ecology in relation to other disciplines has developed well. However, studies about batik pattern rarely analyze the pattern from its ecological point of view. Previous studies about batik motif mostly only discuss its local wisdom. Thus, this article views the motifs from different perspective that is ecological one. Applying literature review and interview methods, it aims to reveal the reason behind each name of Kaliagung Batik motif (a region in Yogyakarta). It was found that the dominant origin of the naming was from Sanskrit language. There were six batik motifs of Kaliagung, namely: Cakiyar Asamaralana, Sungsang Ananta, Gebang Wiguna, Monying Pastika, Dheling Wulung, and Agung Balakosa. Each motif was based on a flora or fauna that existed in Kaliagung area. That flora and fauna had beneficial impact to ecosystem except Agung Balakosa motif since this motif is a compilation from other motifs. In addition, every motif of Kaliagung Batik also had philosophical meaning. Some of them were to be beneficial for others and be humble.